Pedagogical Activities and the Psychological Balance of Personal and Professional Traits - Akhmamat Shermamatovich Jumaev (International Journal on Integrated Education, 2022)
The paper discusses the difficulties in preparing the student for educational action as well as the pedagogical and psychological aspects of the student's professional orientation.